AN ANALYSIS ON TEACHERS' IDENTITY REPRESENTATIONS ON INSTAGRAM - Didin Nuruddin Hidayat; Lili Samrotul Karimah; Alek Alek; Agus Sufyan (UIN Sumatera Utara Medan, 2020)
The teaching profession has been seen as a highly respected job title in some developed countries for bringing significant impacts on the country’s national growth. It is, therefore, teachers are often illustrated into some animations, videos, or pictures on websites and other internet sources. This research aimed to investigate how teachers’ identity is represented on Instagram. 10 Instagram posts related to this issue with the help of Instagram hashtag about #teacherlife were used as the data to get the finding. This research applied the theory and method of Critical Discourse Analysis (CDA) with the perspective of multimodal discourse analysis and social semiotics. The data were analyzed using the sign model of Saussure. Initial coding was also used to analyze the data. After that, the data were then thematized to categorize the data analysis results. The findings of this study revealed that teachers’ identity represented on Instagram provides meaningful insights and offers rich perspectives. It was evident that many ideas of teachers’ identity are against the teachers’ expectations. Four major themes were revealed; they are the teachers’ responsibility, teachers’ commitment, teachers’ authority, and teachers’ needs for recognition. Furthermore, as identity is affected by a significant number of factors, different contexts of teachers may have different identities.